Hearing Protection, Restoration, and Regeneration: An Overview of Emerging Therapeutics for Inner Ear and Central Hearing Disorders - Schilder, Anne G M; Su, Matthew P; Blackshaw, Helen; Lustig, Lawrence; Staecker, Hinrich; Lenarz, Thomas; Safieddine, Saaid; Gomes-Santos, Carina S; Holme, Ralph; Warnecke, Athanasia (Otology & neurotology, 2019)
To provide an overview of biotechnology and pharmaceutical companies active in the field of inner ear and central hearing disorders and their therapeutic approaches. Scientific and grey literature was searched using broad search terms to identify companies and their hearing-related therapeutic approaches. For each approach its lead indication, product, therapeutic modality, target, mechanism of action and current phase of clinical development was collated. A total of 43 biotechnology and pharmaceutical companies have been identified that are developing therapeutics for inner ear and central hearing disorders. Their therapeutics include drug-, cell- and gene-based approaches to prevent hearing loss or its progression, restore hearing, and regenerate the inner ear. Their therapeutic targets and specific mechanisms of action are wide-ranging, reflecting the complexity of the hearing pathways and the diversity of mechanisms underlying inner ear disorders. While none of the novel products under investigation have yet made it to the clinical market, and a large proportion are still at preclinical phase, many therapeutics have already entered clinical testing with more expected to do so in the next few years. A wide range of novel therapeutics targeting different hearing, balance and tinnitus pathways, and patient populations are approaching the clinical domain. It is important that clinicians involved in the care of patients with hearing loss prepare for what may become a radically different approach to the management of hearing disorders, and develop a true understanding of the new therapies' mechanisms of action, applications, and indications.